The influence of ventilation conditions of heat release rate variation over time - Chiojdoiu, Alexandru-Florin; Anghel, Ion; Dragne, Horațiu; Dragomirescu, Andrei; Safta, Carmen-Anca (Technium: Romanian Journal of Applied Sciences and Technology, 2023)
The heat release rate (HRR) is an important parameter in the description of fire evolution. In this paper, the significant influence of ventilation conditions of HRR variation over time is emphasized. This was achieved by: i) performing seven experiments to burn a wood crib on a natural scale, in a confined space using different ventilation scenarios; ii) validation of a fire model by framing the mean value of the HRR parameter error between the results obtained from an experimental test and those obtained from the simulation using the Pyrosim program, in the range of ± 15 % to ± 20 %, within the same ventilation scenario. It has been found that both surface values and types of ventilation opening configurations significantly influence the variation of HRR over time. Thus, both the maximum surface value of the ventilation openings and the use of two types of openings configurations, located diametrically opposite, lead to a maximum value of the HRR. The use of ventilation openings with a low surface value leads to a minimum value of the HRR.